2022
DOI: 10.3390/app12094333
|View full text |Cite
|
Sign up to set email alerts
|

A Scientometric Analysis of Predicting Methods for Identifying the Environmental Risks Caused by Landslides

Abstract: The effects of a landslide can represent a very big problem, including the death of people, damage to the land, environmental pollution and the loss of natural resources. Landslides are the most important medium for transferring sediments and polluting waterways by earth and organic materials. An excess of sediments reduces the quality of fish habitat and the potability of water. In order to understand landslides in depth, a thorough study was conducted using a scientometric analysis, as well as a thorough pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…Because socioeconomic conditions vary from region to region in China, spending on disaster prevention and mitigation varies greatly [ 20 ]. The integrated landslide susceptibility zoning map can further demonstrate the RS and NRS landslide susceptibility in different regions and refine the degree of landslide susceptibility in time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because socioeconomic conditions vary from region to region in China, spending on disaster prevention and mitigation varies greatly [ 20 ]. The integrated landslide susceptibility zoning map can further demonstrate the RS and NRS landslide susceptibility in different regions and refine the degree of landslide susceptibility in time.…”
Section: Discussionmentioning
confidence: 99%
“…By reviewing the previous studies and analyzing the occurrence periods of landslides in previous years, it was found that the landslides in Enshi County mainly occurred in the rainy season (RS), which is significantly higher than the landslides that occurred in the non-rainy season (NRS). Moreover, with the aggravation of global warming and climate change, extreme rainfall in the future is more likely to induce a greater risk of landslide occurrence [ 20 ]. Although the current studies pointed out the different landslide distributions in RS and NRS [ 11 , 13 , 21 , 22 , 23 ], there are very rarely studies conducted on landslide susceptibility assessment (LSA) in different periods by consideration of RS and NRS.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology is provided to help researchers improve systematic review reporting through the use of scientometric analysis. Furthermore, it highlights the complexity of conducting manual searches on database engines [21][22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…Geology, engineering, environmental science, ecology, meteorology, atmospheric science, geochemistry and geophysics, physical science, and water resources are some of the aspects used to study landslides [24]. Furthermore, as shown in Zou and Zheng's [24] keyword mapping, landslides have a large number of linked terms. As a consequence, the research method began by extracting important studies about landslides from the author's perspective.…”
Section: Identification Processmentioning
confidence: 99%